Demonstrations of Pendimethalin for Control of Phalaris minor in Wheat Crop - S. S. Manhas, (Indian Journal of Extension Education, 2017)
The present study was carried out in Barnala district of Punjab during Rabi-2015-16. Front line demonstrations onpendimethalin for control of Phalaris minor in wheat crop were carried out in different farmers' fields. On comparisonwith farmers' practices, it was recorded that the application of pendimethalin @ 1000 ml/acre resulted less Phalaris minordensity, weed dry weight and maximum WCE as compared to other farmers practices viz. Clodinafop @160 to 300 g/acre,Pinoxaden 400 to 500 ml/acre, Sulfosulfuron @ 13 g/acre, Mesosulfuron + Iodosulfuron (Atlantis) @160 to 200 g/acreand Sulfosulfuron + Metsulfuron (Total) @ 16g/acre. Application of pendimethalin @ 1000 ml/acre also result more plantheight, effective tillers, grain yield, net return and B: C ratio as compared other farmers practices. The application ofpendimethalin @ 1000 ml/acre in wheat crop had no residual effect on growth and yield of succeeding crop (fodder maize,sesbania, rice, moong and cotton) as responded by 85 farmers. Lack of knowledge about pendimethalin for weed controlin wheat (18.8%), fear of low benefit: cost ratio (16.5%), busy schedule at the time of sowing (14.1%), lack of guidance forpendimethalin application (11.8%), fear of ineffectiveness of pendimethalin (10.6%) were the major reasons towardsnon-adoption. Publicising the details in respect to dose, time and method of application and intensive training programmeon herbicide use in farmers' field were felt as some crucial steps for increasing the adoption level.